Tatalaksana Anestesi Pada Large Aortopulmonary Window, Pulmonary Hypertension, Dan Patent Foramen Ovale Yang Dilakukan Operasi Operasi Ap Window Closure Dan Pfo Dipertahankan - Rizal, Anugrah Danang Ifnu; Fakhrudin Nur, Rifdhani; Pratomo, Bhirowo Yudo (Jurnal Locus Penelitian dan Pengabdian, 2025)
Aortopulmonary window (AP window) is a rare congenital heart defect (0.2%-0.6%), due to failure of the conotruncal septum, and should be repaired as early as possible, ideally before 3 months of age, to prevent irreversible pulmonary hypertension (PH), heart failure, and death. We report a 2-year-6-month-old boy with a large aortopulmonary window, high flow–high resistance pulmonary hypertension (PH), and atrial septal defect/patent foramen ovale (ASD/PFO). Echocardiography showed a 13–15 mm AP window, left-to-right shunt, PFO, and 17 mm Tricuspid Annular Plane Systolic Excursion (TAPSE). CT scan detected an 8 mm ASD primum, PH, bilateral pneumonia, and minimal pericardial effusion. Catheterization showed high-flow-high-resistance PH. The patient was planned for aortopulmonary (AP) window closure and patent foramen ovale (PFO) was maintained under general anesthesia. Preoperative management involves a thorough evaluation, with premedication given in the form of midazolam 1 mg and induction using fentanyl 40 mcg and rocuronium 10 mg. Intubation was successful, SIMV-PC ventilation was maintained optimally (SpO? 99–100%). Invasive monitoring was used (ECG, TEE, arterial line, and CVC). During cardiopulmonary bypass (CPB) there was no severe hypoperfusion, but post-CPB there was severe vasoplegia and mild respiratory acidosis, managed with milrinone. Postoperative care focused on maintaining adequate cardiac output. Coagulation disorders were managed with FFP, PRC, and tranexamic acid. Pulmonary hypertension was prevented with high FiO? and correction of acidosis. Ventilator weaning was performed gradually and stably.